2019
DOI: 10.4070/kcj.2018.0246
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cardiac Magnetic Resonance Imaging

Abstract: Cardiac magnetic resonance (CMR) imaging provides accurate anatomic information and advanced soft contrast, making it the reference standard for assessing cardiac volumes and systolic function. In this review, we summarize the recent advances in CMR sequences. New technical development has widened the use of CMR imaging beyond the simple characterization of myocardial scars and assessment of contractility. These novel CMR sequences offer comprehensive assessments of coronary plaque characterization, myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 99 publications
0
13
0
1
Order By: Relevance
“…As for the temporal progression, CMR T2 mapping assesses myocardial edema due to an inflammatory process that is usually reversible. 8,9 However, this case did not present T2 images compatible with myocardial edema but rather with fibrosis, determining a subacute phase. Left ventricular dilation is also compatible with subacute myocarditis since the onset of negative remodeling occurs days or weeks after the initial myocardial injury.…”
Section: Case Reportmentioning
confidence: 66%
“…As for the temporal progression, CMR T2 mapping assesses myocardial edema due to an inflammatory process that is usually reversible. 8,9 However, this case did not present T2 images compatible with myocardial edema but rather with fibrosis, determining a subacute phase. Left ventricular dilation is also compatible with subacute myocarditis since the onset of negative remodeling occurs days or weeks after the initial myocardial injury.…”
Section: Case Reportmentioning
confidence: 66%
“…che�ical exchan�e sat�ration transfer, 2000ті роки), напруга міокарда (англ. strain, 2010-ті роки) і чотиривимірне сканування з одночасним зображенням структури та кровоплину (2010-ті роки) [14,[25][26][27][28].…”
Section: променева діагностика (хх-ххі ст)unclassified
“…Proof-of-concept studies have shown the promise of this approach for guiding AF ablation, and initial randomized trials comparing simulation-guided versus standard clinical therapy are ongoing ( 119 ). With these recent advances, CMR imaging can provide comprehensive images of the heart in patients with various cardiac diseases, adding prognostic value ( 212 ).…”
Section: Characterizing Atrial Structural Remodeling By Non-invasive ...mentioning
confidence: 99%